Konstruksi Sosial tentang Dukungan Organisasi : Studi Fenomenologi Sosial terhadap Keterlibatan Kerja Tenaga Kerja Sosial di Dinas Sosial Kota Malang - Kartika Candra Kirana; Nasharuddin Mas; Choirul Anam (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
In the modern work environment, perceived organizational support is an important factor in increasing work engagement and productivity. Organizations that provide emotional, professional, and structural support to employees tend to have a more motivated, loyal, and productive workforce. However, social workers, especially in the Malang City Social Service, often experience minimal organizational support, resulting in work stress, burnout, and high employee turnover. Most previous studies have used a quantitative approach, while few have examined how organizational support is socially constructed in everyday interactions. This study aims to understand how social workers in the Malang City Social Service construct the meaning of organizational support and how it affects their work engagement. This study uses a qualitative approach with a social phenomenology method. Data were collected through in-depth interviews, participant observation, and document analysis, with informants selected using homogeneous purposive sampling. The findings of the visualization construct confirm that effective organizational support acts as a catalyst in increasing work engagement, strengthening motivation, and improving the performance and productivity of social workers in the public service organization environment. Organizational support is not only an administrative aspect, but also a social phenomenon that is formed through interaction, communication, and work experience. These findings contribute to the social phenomenology literature in organizational management studies, as well as provide recommendations for social organizations to improve the well-being and engagement of social workers.